A Roma founder BIN1 mutation causes a novel phenotype of centronuclear myopathy with rigid spine. (24th July 2018) - Cabrera-Serrano, Macarena; Mavillard, Fabiola; Biancalana, Valerie; Rivas, Eloy; Morar, Bharti; Hernández-Laín, Aurelio; Olive, Montse; Muelas, Nuria; Khan, Eduardo; Carvajal, Alejandra; Quiroga, Pablo; Diaz-Manera, Jordi; et al.
Abstract : Objective: To describe a large series of BIN1 patients, in which a novel founder mutation in the Roma population of southern Spain has been identified. Methods: Patients diagnosed with centronuclear myopathy (CNM) at 5 major reference centers for neuromuscular disease in Spain (n = 53) were screened for BIN1 mutations. Clinical, histologic, radiologic, and genetic features were analyzed. Results: Eighteen patients from 13 families carried the p.Arg234Cys variant; 16 of them were homozygous for it and 2 had compound heterozygous p.Arg234Cys/p.Arg145Cys mutations. Both BIN1 variants have only been identified in Roma, causing 100% of CNM in this ethnic group in our cohort. The haplotype analysis confirmed all families are related. In addition to clinical features typical of CNM, such as proximal limb weakness and ophthalmoplegia, most patients in our cohort presented with prominent axial weakness, often associated with rigid spine. Severe fat replacement of paravertebral muscles was demonstrated by muscle imaging. This phenotype seems to be specific to the p.Arg234Cys mutation, not reported in other BIN1 mutations. Extreme clinical variability was observed in the 2 compound heterozygous patients for the p.Arg234Cys/p.Arg145Cys mutations, from a congenital onset with catastrophic outcome to a late-onset disease. Screening of European Roma controls (n = 758) for the p.Arg234Cys variant identified a carrier frequency of 3.5% among the Spanish Roma. Conclusion: We have identified a BIN1 founder Roma mutation associated with a highly specific phenotype, which is, from the present cohort, the main cause of CNM in Spain.